Possible formation of pulmonary microthrombi in the early puerperium of pregnant women critically ill with COVID-19: Two case reports (2020)
Background: Limited data are available on the management of pregnant women with severe or critical forms of COVID-19, such as the optimal timing of provider-initiated delivery, and post-partum care, including antithrombotic prophylaxis. We present the clinical course, pre- and post-partum management, and outcomes of two pregnant women critically ill with COVID-19. Cases: Both women had confirmed SARS-CoV-2 pneumonia with rapid clinical decompensation that required admission to the intensive care unit, intubation, and delivery by emergency cesarean section at 32 and 29 weeks. Both patients clinically improved in the first two postoperative days, but this was followed by clinical, laboratory and radiological deterioration on the third postoperative day; however, they both improved again after full anticoagulation. This pattern suggests the possible formation of pulmonary microthrombi in the early puerperium. We discuss the challenges faced by the multiprofessional team in the management of these patients. Conclusions: There are few resources to guide health professionals caring for pregnant women with critical COVID-19. These two cases contribute to the rapidly evolving knowledge on the management and outcomes of pregnant women with COVID-19.